2021
DOI: 10.1186/s12886-021-01980-w
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in choroidal blood flow after half and one-third dose verteporfin photodynamic therapy for chronic central serous chorioretinopathy

Abstract: Background The effect of various reduced doses of verteporfin photodynamic therapy (PDT) on choroidal blood flow in chronic central serous chorioretinopathy (CSC) remains unclear. Therefore, this study aimed to evaluate choroidal blood flow after half-dose PDT (1/2PDT) and one-third dose PDT (1/3PDT) with verteporfin for chronic CSC using laser speckle flowgraphy and spectral-domain optical coherence tomography. Methods Twenty-seven eyes of 27 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Pathological studies have demonstrated that PDT can occlude CNV and choriocapillaris without damaging choroidal large vessels [ 28 ]. Kumashiro et al reported that choroidal blood flow decreased in CSC patients after PDT-irradiation [ 13 ]. Based on these results, it is reasonable that the decrease in CT in and around the irradiated area can be explained as a result of the reduction of choroidal volume caused by PDT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pathological studies have demonstrated that PDT can occlude CNV and choriocapillaris without damaging choroidal large vessels [ 28 ]. Kumashiro et al reported that choroidal blood flow decreased in CSC patients after PDT-irradiation [ 13 ]. Based on these results, it is reasonable that the decrease in CT in and around the irradiated area can be explained as a result of the reduction of choroidal volume caused by PDT.…”
Section: Discussionmentioning
confidence: 99%
“…Our evaluations of Haller’s vessels asymmetry were subjective. Additionally, we used OCT to evaluate changes based on morphological characteristics; blood flow was not quantified using laser speckle fundus flowgraphy [ 13 ]. In future research, it would be desirable to combine OCT and laser speckle flowgraphy in a larger sample size; prospective research is desirable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the primary pathogenesis of chronic CSC is speculated to be shifting to a localized area of choroidal hyperpermeability, although a thickened sclera and choroidal hyperperfusion may trigger the onset of CSC. With regard to the choroidal hemodynamics after half-dose PDT for CSC, Kumashiro et al reported that the macular MBR decreased after treatment; this effect was blunted by 1/3-dose PDT 20 . In the current study, the MBR in the PDT irradiation area was signi cantly decreased after half-dose PDT, which is consistent with the report by Kumashiro et al In addition, the current study showed that the MBR did not change in the untreated fellow eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the primary pathogenesis of chronic CSC is speculated to be shifting to a localized area of choroidal hyperpermeability and RPE disturbance associated with localized blood flow alteration, although a thickened sclera and choroidal hyperperfusion may trigger the onset of CSC. With regard to the choroidal hemodynamics after half-dose PDT for CSC, Kumashiro et al reported that the macular MBR decreased after treatment; this effect was blunted by 1/3-dose PDT 20 . In the current study, the MBR in the PDT irradiation area was significantly decreased after half-dose PDT, which is consistent with the report by Kumashiro et al In addition, the current study showed that the MBR did not change in the untreated fellow eyes.…”
Section: Discussionmentioning
confidence: 99%